Therapeutic Drug Monitoring in Buprenorphine/Naloxone Treatment for Opioid Use Disorder: Clinical Feasibility and Optimizing Assay Precision - Elarabi, Hesham Farouk; Hasan, Nael; Marsden, John; Radwan, Doaa; Adem, Abdu; Almamari, Samya; Elrasheed, Abuelgasim (Pharmacopsychiatry, 2020)
Introduction Compliance with sublingual buprenorphine/naloxone (SL-BUP/NX) is associated with higher abstinence from illicit opioid use. Therapeutic drug monitoring (TDM) has been recommended for adherence monitoring of buprenorphine (BUP) maintenance treatment for opioid use disorder (OUD), but to date there have been no reported clinical applications. In this TDM feasibility study, we investigated BUP assay precision in 15 adults with OUD who had been stabilized on buprenorphine/naloxone.Methods Using solid phase extraction, BUP recovery was contrasted at 100 mMol and 1 Molar of acetic acid wash solution. Precision was determined by applying the condition generating highest recovery using 0.2 ng/mL and 10 ng/mL standards. Four blood samples were drawn to examine the BUP peak and trough plasma concentrations, and BUP elimination rate was estimated. BUP recovery was examined again in a random sample and contrasted with the concentration predicted applying first-order kinetics.Results Higher BUP recovery was achieved with 1 Molar wash (94.3%; p=0.05). Precision ranged from 15–20%. The estimated limit of detection (LoD) and limit of quantitation (LoQ) were 0.02 and 0.069 ng/mL, respectively. BUP peak and trough concentrations were successfully examined, and BUP trough concentrations were replicated confirming steady state. BUP concentrations were predicted at a variance of −7.20% to 1.54 %.Conclusions TDM for BUP maintenance treatment of OUD is feasible, and simple adjustment of the assay conditions enhances BUP recovery.
Keywords: opioid dependence; therapeutic drug monitoring; validation; feasibility